Reappraisal generation after acquired brain damage: The role of laterality and cognitive control - Salas Riquelme, Christian E.; Turnbull, Oliver H.; Gross, James J. (Frontiers in Psychology, 2014)
In the past decade, there has been growing interest in the neuroanatomical and neuropsychological bases of reappraisal. Findings suggest that reappraisal activates a set of areas in the left hemisphere (LH), which are commonly associated with language abilities and verbally mediated cognitive control. The main goal of this study was to investigate whether individuals with focal damage to the LH (n = 8) were more markedly impaired on a reappraisal generation task than individuals with right hemisphere lesions (RH, n = 8), and healthy controls (HC, n = 14). The reappraisal generation task consisted of a set of ten pictures from the IAPS, depicting negative events of different sorts. Participants were asked to quickly generate as many positive reinterpretations as possible for each picture. Two scores were derived from this task, namely difficulty and productivity. A second goal of this study was to explore which cognitive control processes were associated with performance on the reappraisal task. For this purpose, participants were assessed on several measures of cognitive control. Findings indicated that reappraisal difficulty – defined as the time taken to generate a first reappraisal – did not differ between LH and RH groups. However, differences were found between patients with brain injury (LH + RH) and HC, suggesting that brain damage in either hemisphere influences reappraisal difficulty. No differences in reappraisal productivity were found across groups, suggesting that neurological groups and HC are equally productive when time constraints are not considered. Finally, only two cognitive control processes inhibition and verbal fluency- were inversely associated with reappraisal difficulty. Implications for the neuroanatomical and neuropsychological bases of reappraisal generation are discussed, and implications for neuro-rehabilitation are considered.